Analisis no parametrico de eficiencia en explotaciones lecheras - Gonzalez Fidalgo, E.=700 1 Alvarez Pinilla, A.; Arias Sanpedro, C.
(Es, En)
ilus., 14 ref.
Keywords: EXPLOTACIONES AGRARIAS; PRODUCCION LECHERA; TECNOLOGIA; ESPAÑA; EFICIENCIA